2013
DOI: 10.1093/annonc/mdt254
|View full text |Cite
|
Sign up to set email alerts
|

Results of a phase II pilot study of moderate dose radiotherapy for inoperable desmoid-type fibromatosis—an EORTC STBSG and ROG study (EORTC 62991–22998)

Abstract: Moderate dose radiotherapy is an effective treatment of patients with DF. Response after radiation therapy is slow with continuing regression seen even after 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
89
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 14 publications
5
89
0
6
Order By: Relevance
“…They reported that the 3 year LC rate was 81.5%. Acute and late side effects were acceptable (27). In our series, the only significant factor for local control was radiotherapy dose.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…They reported that the 3 year LC rate was 81.5%. Acute and late side effects were acceptable (27). In our series, the only significant factor for local control was radiotherapy dose.…”
Section: Discussionmentioning
confidence: 50%
“…If there is progression, surgery and/or RT should be the subsequent choice. Therefore, the unnecessary complications of radiotherapy and surgery may be avoided (25)(26)(27). Others have recommended chemotherapy or systemic therapy (such as hormonal therapy, non-steroidal anti-inflammatory therapy or targeted therapy) in patients with advanced unresectable tumors or recurrent disease after surgery and/ or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The head and neck localization is not common and is mostly sporadic (6) . During 40 years only 179 cases were reported (5) .Parotid localization has been very rarely treated; they have tried to separate it from that arising from other parts of the body (10) , due to its relation to its critical anatomical position (4) . The peak incidence is situating about the third decade (5,6) ; our patient was younger 24 years.…”
Section: Discussionmentioning
confidence: 99%
“…Deep fibromatosis may reach a large size; it generally appears as a mass characterized by being: painless, ill-defined, firm, non-inflammatory, deeply located, fixed to the underlying structures, and which grow slowly (2,4,6) . The natural biological behavior of deep fibromatosis can be unpredictable and variable (10) ; that means that a significant proportion (about 50%) of patients have tumors that remain spontaneously stable after initial progression or even regress and hence benefit from a front line non-aggressive policy (watch and wait) (10) . This spontaneous regression has been observed in the menarche and menopause (5) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation